DURABLE FINANCING OF THE ROMANIAN HEALTHCARE SYSTEM WITHIN THE EUROPEAN BACKGROUND - Antohi, Valentin; Cojocaru, Gabriel (European Scientific Journal, ESJ, 2015)
All healthcare systems in the world confront themselves with an obvious discrepancy between the need for medical services, and the available sustainable financial resources for covering this increasing need for healthcare. This has become a reality which has led to an intense preoccupation on the part of all-acting participants within the healthcare systems. This aim of this study is to find solutions to make financial resources more efficient, starting with the process of caring for patients, and ending with covering up the expenses within the system. Even if there are continuous reforms happening in most of the states in Europe and/or the world, we can surely state that there is no health system deemed perfect that can be copied or adapted to. This is due to the fact that each state confronts itself with different situations in the health issue, related to making financing efficient, optimizing, well allocated, and used as intended for healthcare.